Responsible Use of LLM Models for Labor Market Foresight: The Experience of a Vocational Education and Training Institution - Braga, Cicero; Lima, Yuri; Pereira, Inês (Anais da Conferência Latino-Americana de Ética em Inteligência Artificial (LAAI-Ethics); 2024: Anais da 1ª Conferência Latino-Americana de Ética em Inteligência Artificial, 2024)
This article examines the experience of a Vocational Education and Training institution in utilizing Artificial Intelligence to analyze labor market dynamics and guide the provision of VET programs. It presents the structuring of methodologies capable of delivering efficient and robust results, derived from large datasets, in an ethical and responsible manner.